2011
DOI: 10.1007/s00540-011-1261-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of oral rehydration therapy until 2 h before surgery: a multicenter randomized controlled trial

Abstract: PurposeIn many countries, patients are generally allowed to have clear fluids until 2–3 h before surgery. In Japan, long preoperative fasting is still common practice. To shorten the preoperative fasting period in Japan, we tested the safety and efficacy of oral rehydration therapy until 2 h before surgery.MethodsThree hundred low-risk patients scheduled for morning surgery in six university-affiliated hospitals were randomly assigned to an oral rehydration solution (ORS) group or to a fasting group. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 18 publications
2
43
0
3
Order By: Relevance
“…A multicenter clinical study found that oral rehydration therapy until 2 h before surgery was safe and feasible in the low-risk Japanese surgical population. Physicians are encouraged to use this practice to maintain the amount of water in the body and electrolytes and to improve the patient's comfort [35]. Continuous epidural analgesia is effective for the treatment of postoperative intestinal paralysis.…”
Section: Discussionmentioning
confidence: 98%
“…A multicenter clinical study found that oral rehydration therapy until 2 h before surgery was safe and feasible in the low-risk Japanese surgical population. Physicians are encouraged to use this practice to maintain the amount of water in the body and electrolytes and to improve the patient's comfort [35]. Continuous epidural analgesia is effective for the treatment of postoperative intestinal paralysis.…”
Section: Discussionmentioning
confidence: 98%
“…Benzer bir çalışmada, düşük riskli hastalara ameliyattan 2 saat öncesinde oral rehidratasyon sıvısı verilmesinin hastaların preoperatif dönemde duyduğu açlık ve susuzluk hissini azaltan, güvenli bir yöntem olduğu gösterilmiştir. 12 Mide rezidüel volümünün 25 ml'nin üstünde ve pH değerinin de 2,5'in altında olduğu hastalar, anestezi indüksiyonu aşamasında pulmoner aspirasyon açısından riskli kabul edilmektedir. 7,8 Çalış-mamızda aç kalma süresinin artışıyla paralel olarak mide rezidüel volümünün arttığı gösterilmiştir.…”
Section: Discussionunclassified
“…15 Japonya'da 2003 yılında anestezi eğitimi verilen hastanelerde aç kalma süresi ortalamaları öğle-den önceki vakalarda 9 saat, öğleden sonraki vakalarda 6 saat olarak tespit edilmiştir. 12 Ülke-mizde halen birçok merkezde öğleden sonraki vakalara sabah öğünü verme alışkanlığı olmadığın-dan, aç kalma süreleri çok uzayabilmektedir. Bizim çalışmamızda öğleden sonraya kalan vakaların ortalama 15-16 saati bulan açlık ve susuzluk süreleri olduğu saptanmıştır.…”
Section: Discussionunclassified
“…ORS contains 2.5% carbohydrate and 50 mmol·L -1 sodium ions. Preoperative body fluid management with ORS is known as preoperative oral rehydration therapy (ORT) and is widely practiced in Japan instead of infusion therapy 14,15. In our hospital, patients are asked to drink 1500 mL of ORS packaged in 500-mL plastic bottles (OS-1, Otsuka Pharmaceutical Factory, Inc., Tokushima, Japan) for preoperative fluid and electrolyte replacement.…”
Section: Methodsmentioning
confidence: 99%